Where there's smoke: The library's role in bibliographic analysis of academic misconduct - Seeland, Josh (Canadian Perspectives on Academic Integrity, 2022)
Literature from many disciplines has, for years, called for library involvement in academic integrity. More recently, it has been suggested that libraries and those working in them are well-suited to assist in detecting plagiarism. At the same time, literature specific to quality in academic libraries has emphasized the development of and focus on services, and what libraries do rather than what they have. With this in mind, and with academic integrity in its portfolio, the Library at Assiniboine Community College has added a new service to the identification stage of its holistic approach to academic integrity. Combining existing resources on bibliographic forensics, text-matching software, and discovery interviews, it allows for the library to leverage its unique knowledge of available resources in identifying academic misconduct. Learning Outcomes Summarize frameworks and resources that inform this service Examine opportunities for libraries in performing bibliographic analysis related to potential academic misconduct cases Reflect on the implementation and evaluation of this service